Considering Aspects on Selecting ESP Teachers - Koifman, Clara S.; Justo, Elisabeth A. C.; Kerr, Lilian (The ESPecialist, 2012)
This paper is meant to lead ESP approach followers to reflect on the profile of an ESP teacher as well as on their own ideas and practices. It is also meant to launch procedures for choosing teachers with adequate competence to become ESP professionals. As we are not interested in only finding out about linguistic and pedagogical knowledge, we changed the traditional way of selecting teachers, filtering also their feelings, their way of thinking about what happens in the classroom and their way of looking at their students as human beings. Our intention is to clarify doubts that may occur about the purposes, design, practice, criteria for evaluation, and the legal structure that sustained the examination which was meant to choose candidates for a post as an English for Specific Purpose Teacher at E.T.F.Q.-R.J. We also took into account the pedagogical philosophy and necessities of the school, the team of English teachers, the pedagogical practice as well as the target clientele, the future professionals. We will go through the test analysing the needs, the steps and the results going into details that reflect our priorities when devising the ten questions that compose the written test and all the issues linked to the nature of such innovating work. We also make a self-evaluation as we consider some aspects to be altered and developed.